Sytuacja społeczna ludzi starych jako problem pedagogiczny - Tabaczkiewicz-Paech, Astrid (Wydawnictwo Naukowe UAM w Poznaniu, 1992)
In the article were presented results and analysis of searches of social situation of older people. A general purpose of searches was to qualify outer impulses which are components of aspect of social situation and that how it is accepted by older people and how it stimulates their activity. Learning of social situation of older people allows to qualify specific methods of work with them on base of pedagogics.
A social situation of old people as a pedagogic problem
Keywords: sytuacja społeczna; social situation; pedagogika społeczna; social pedagogy; ludzie starzy; old people; badania; research